All Visual, all the Time: Towards a Theory of Visual Practices for Pastoral Theological Reflection - Waters, Sonia (Pastoral psychology, 2016)
Visual culture deeply influences those whom pastoral care providers serve, and contemporary practices with images complicate images' contribution to personal or social suffering. I begin by describing the mobile, networked dynamics of contemporary visual practices, which include receiving but also creating, curating, and sharing images in emergent and shifting visual communities. I then utilize visual studies theorist Gary Shapiro's concept of visual regimes, outlining how images work as a kind of soft power that influences the social construction of meaning. I illustrate these practices through a selection of images surrounding the police shooting of Michael Brown by officer Darren Wilson in Ferguson, Missouri, and the protests and online debates that arose from that tragic event. I suggest throughout this paper that images play a major part in the social construction of subjective worlds and thus contribute both to our suffering and to the meaning we make from our suffering.